Studies on the Mechanism whereby Platelets are Clumped by Adenosine Diphosphate - Spaet, Th. H; Lejnieks, Ilze (Thrombosis and Haemostasis, 1966)
The effect of platelets on C14-labeled adenosine diphosphate (ADP) was studied. It was found that :1. A small amount of radioactive ADP in platelet-rich plasma became irreversibly bound to platelets, but on extraction radioactivity was found as a conversion mixture of adenine nucleotides resembling that in the platelet pool. Red cells showed similar binding and conversion, but only platelets were clumped by ADP. Nucleotides with little or no clumping activity (ATP, AMP and adenosine) bound to platelets and red cells in a manner similar to that of ADP, and they also yielded similar intracellular conversion products.2. Platelet-poor plasma converted ADP into adenosine monophosphate (AMP), but this activity was destroyed at 56° C in 10 minutes. Heated, platelet- poor plasma was a suitable medium for washing and suspending platelets in these studies.3. Platelets washed and suspended in heated plasma were clumped by ADP and produced ADP-dephosphorylation only in the presence of divalent cation. Red cells showed no ability to dephosphorylate ADP in this system.4. Platelets washed in saline or studied in the presence of excess AMP were not clumped by ADP nor did they yield ADP-dephosphorylation. Benadryl inhibited platelet clumping, but was without effect on ADP-dephosphorylation.It is suggested that ADP clumps platelets by serving as an energy source to activate a binding reaction as yet unidentified.